IMAM Model: Integrating Dick and Carey with Blended Learning for Student Autonomy - Imam Mashudi; Ismail Tahir (Fakultas Ilmu Pendidikan dan Budaya - Universitas Bina Mandiri Gorontalo, 2026)
Educational research has established student autonomy as its primary area of investigation. However, few studies have developed instructional models to enhance student autonomy in higher education settings. This study proposes IMAM as an instructional model that unites blended learning principles with Dick and Carey’s approach to fostering student independence. This study adopts a research and development (R&D) methodology by distributing questionnaires to Bina Mandiri Gorontalo University’s entrepreneurship lecturers. In addition, the data were analysed quantitatively to identify trends and patterns among lecturers in implementing the IMAM model. The results show that student autonomy improves significantly through the four structured phases of the IMAM model: identification of learning needs, classroom management, adaptive and active learning integration, and independent learning development. Through this study, these findings are expected to increase student independence in learning in higher education in Indonesia and inform relevant and sustainable policymaking. The study provides implications for curriculum developers, educators, and policymakers to improve educational guidance and instructions with the need to cultivate lifelong learning competencies among Indonesian students.